Pengembangan LMS Berbasis Moodle Untuk Meningkatkan Kompetensi Programmer Menggunakan Project Based Learning Mengimplementasikan Computational Thinking Pada Elemen Pemrograman Java - Dimas Adiz Setiawan; Bambang Sujatmiko (CV. SINAR HOWUHOWU, 2026)
Learning in the digital era requires students to have competencies relevant to the needs of the workplace. Observations at SMKN Jatirogo show that Object-Oriented Programming (Java) learning for class XI RPL is still dominated by independent practice without project-based learning, with an average daily test of only 42, far below the KKM of 80, so that students' computational thinking skills and programmer competencies have not developed optimally. This study aims to describe the steps for developing a Moodle-based Learning Management System (LMS) using Project Based Learning (PjBL) that implements Computational Thinking, and to analyze the differences in programmer competency improvement between classes using LMS and conventional classes. The research method uses a Research and Development (R&D) approach with the ADDIE model and a quasi-experimental design, with class XI RPL 2 as the experimental class and XI RPL 3 as the control class. Data were analyzed using percentages for product feasibility, ANCOVA for cognitive learning outcomes, and Mann-Whitney U Test for psychomotor learning outcomes. The results showed that the LMS PEVA obtained 88% validity (very valid) with all system functions running well. ANCOVA test showed a significant cognitive difference (Sig. 0.020 < 0.05; F = 5.680), while the average posttest psychomotor of the experimental class (76.71) was higher than the control class (57.25) (Sig. 0.000 < 0.05). These findings indicate that the Moodle-based LMS that integrates PjBL and Computational Thinking is feasible to use and effective in strengthening students' programmer competencies, especially in Java programming practice skills.